2015
DOI: 10.4137/sart.s22440
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Seeking as a Phenotypic Marker of Adolescent Substance Use

Abstract: Trait novelty seeking has been consistently implicated in substance use, yet the origins and mechanisms of novelty seeking in substance use proneness are unclear. We aimed to characterize novelty seeking as a phenotypic marker of substance use proneness in adolescence, a critical period for drug use experimentation. To this end, we parsed novelty seeking’s two constituent subdimensions – exploratory excitability (drive for novel experience) and impulsiveness (careless decision-making) – and explored the indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 62 publications
3
23
0
2
Order By: Relevance
“…This suggests that high sensation seeking may contribute to a strong liability to developing AUP, over and above the effects of negative emotionality, extraversion, conscientiousness, agreeableness, and openness/imagination. The indirect effect of PRS on AUP through sensation seeking converges with recent evidence regarding the possibility of shared genetic variation between sensation seeking and AUP (Aliev et al, 2015) and is consistent with the broader molecular literature regarding the role of sensation seeking as a possible endophenotype for adolescent substance use (Bidwell et al, 2015). For instance, molecular genetic studies have found that sensation seeking mediated the association between a variable number of tandem repeat polymorphism in the DRD4 gene and alcohol-related outcomes in adolescents and collegeaged adults (Laucht et al, 2007;Ray et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This suggests that high sensation seeking may contribute to a strong liability to developing AUP, over and above the effects of negative emotionality, extraversion, conscientiousness, agreeableness, and openness/imagination. The indirect effect of PRS on AUP through sensation seeking converges with recent evidence regarding the possibility of shared genetic variation between sensation seeking and AUP (Aliev et al, 2015) and is consistent with the broader molecular literature regarding the role of sensation seeking as a possible endophenotype for adolescent substance use (Bidwell et al, 2015). For instance, molecular genetic studies have found that sensation seeking mediated the association between a variable number of tandem repeat polymorphism in the DRD4 gene and alcohol-related outcomes in adolescents and collegeaged adults (Laucht et al, 2007;Ray et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…Sensation seeking is characterized by a tendency to seek out novel sensations and experiences (see reviews by Hittner &Swickert, 2006, andDick et al, 2010) and has been well studied in the development of AUP during adolescence (Ibáñez et al, 2008;Martin et al, 2002). High sensation seeking is associated with an earlier onset of alcohol use (Jurk et al, 2015;Viken et al, 2007;Zuckerman, 1994) and has been shown to mediate the association between early risk factors, such as family histories of substance use, and later AUP (Bidwell et al, 2015;Dick et al, 2013). High sensation seeking may also be transmitted along with risk for alcohol-related outcomes, as one large family-based study found that novelty seeking was more strongly associated with alcohol dependence among individuals with at least one parent diagnosed with alcohol dependence than in individuals without an alcohol-dependent parent (Grucza & Bierut, 2006).…”
mentioning
confidence: 99%
“…Additionally, it is not surprising that we found higher NS scores in young individuals since risk taking behaviors and Novelty Seeking are considered a typical adolescent's behavior (Kelley et al, 2004). This is also in line with the evidence reported by Andriola et al (2011) and Bidwell et al (2015) which suggested that higher scores in NS were associated with typical behaviors found in adolescents, including conduct problems and a higher tendency to experiment with drugs. A similar but less pronounced trend was found in HA scores which tended to decrease with age, with higher scores in adolescents and lower scores in adults (18-49) but with an upturn in old adults (50-69).…”
Section: Temperament Dimensionssupporting
confidence: 90%
“…Subsequently, genetic determinants of receptor expression and neuronal function in the normal variation of human behavior have been validated (2). Several temperament and personality traits, including novelty seeking (NS), harm avoidance, and impulsivity, have been associated with the vulnerability to mental illnesses (3,4) and have been directly related to receptors and neurotransmission using functional imaging (5)(6)(7). In parallel, dysregulation or disequilibrium of brain neurotransmitters have repeatedly been linked to mental diseases.…”
mentioning
confidence: 99%